Analytical and Bioanalytical Methods for the Determination of Dipeptidyl Peptidase-4 Inhibitors in Various Matrices: A Comprehensive Review - Hadawale, Sakshi; Sharma, Sanjay (Current Diabetes Reviews, 2025)
BackgroundDPP-4 inhibitors, or gliptins, are new oral antidiabetic drugs for type 2 diabetes. They help to regulate insulin and glucagon. These drugs have the advantage of a lower risk of hypoglycemia compared to some other diabetes medications and are typically prescribed when metformin and sulphonylureas have become less effective.ObjectiveThis review analyses a range of analytical and bioanalytical methods for DPP-4 inhibitors, that use spectroscopic techniques, chromatographic, and hyphenated techniques for analysis. So far, no review comprising all DPP-4 inhibitors has been presented. The primary objective of this review is to present the analysts with various analytical and bioanalytical methods for the quantification and estimation of DPP-4 inhibitors in different matrices.MethodsTo improve understanding, a review was carried out by creating a database of pre-existing research from digital sources such as ScienceDirect, and PubMed. The methodology is shown in the flowchart of the literature selection process.ConclusionThe comprehensive assessment of methods for analysing DPP-4 inhibitors can be a valuable resource for researchers and healthcare practitioners. Hitherto, no review encompassing all DPP-4 inhibitors has been presented. Therefore, gaps in the data available on a particular subject, need to be required to collect data on a particular construct. The review suggests that chromatographic techniques were majorly used for analysis wherein solvents like acetonitrile, methanol, and buffer solutions were used as mobile phases that can deteriorate HPLC columns and equipment. So, scientists could investigate new methods for the assessment of DPP-4 inhibitors using more eco-friendly solvents.
Keywords: HPLC